Nonlinear Influence of Working Capital Management on Profitability of Tourism Firms: Panel Data Evidence from Developed and Developing Countries - Ersoy, Ersan; Işık, Özcan; Günay, Fatih (Anais Brasileiros de Estudos Turísticos, 2022)
Having an optimal working capital level can balance firms’ costs and benefits and maximizes their profitability. This study examines the influence of working capital management (WCM) on profitability (ROA) in tourism sub-sectors in 74 countries between 2005 and 2017 in terms of the countries’ development levels. Findings from the fixed-effects panel data regression models indicate that there exists an inverted U-shaped association between WCM and ROA in the tourism industry around the world. However, when we consider the development levels of the countries, our empirical results show that an inverted U-shaped nonlinear association between WCM and ROA is more valid in tourism sub-industries in developing countries. Moreover, our empirical findings for tourism sub-industries in developed countries show the existence of a positive linear relationship between WCM and ROA for H&M and F&B firms, but a non-linear U-shaped association between WCM and ROA for L&R firms. The findings from this paper offer important implications for managers working in the tourism industry in both developed and developing countries to improve the use of working capital.